Evaluating English Language Textbooks through Tomlinson’s Theory: A Systematic Review - Andrew Panji Damai; Rina Listia; Elsa Rosalina (Universitas Lambung Mangkurat, 2025)
This study aims to examine the strengths and limitations of English language textbooks as identified in a range of scholarly publications focused on content analysis of instructional materials. Numerous textbooks—whether produced by governmental or independent publishers—have been evaluated through various theoretical lenses, with Brian Tomlinson’s comprehensive framework being one of the most frequently employed. Utilizing a systematic literature review, this research critically explores the pedagogical merits and shortcomings embedded within English textbooks or coursebooks as documented across the selected studies. A total of eight peer-reviewed articles published between 2018 and 2025 were analyzed using Tomlinson’s evaluative criteria. The objective of this research is to determine wether Tomlinson’s Theory is effective to develop a good textbook. The findings indicate that while the majority of textbooks demonstrated strong alignment with Tomlinson’s principles. The comprehensive analysis of the findings categorized as